2022
DOI: 10.3389/fendo.2022.965890
|View full text |Cite
|
Sign up to set email alerts
|

Factors correlated with targeted prevention for prediabetes classified by impaired fasting glucose, impaired glucose tolerance, and elevated HbA1c: A population-based longitudinal study

Abstract: BackgroundThere is still controversy surrounding the precise characterization of prediabetic population. We aim to identify and examine factors of demographic, behavioral, clinical, and biochemical characteristics, and obesity indicators (anthropometric characteristics and anthropometric prediction equation) for prediabetes according to different definition criteria of the American Diabetes Association (ADA) in the Chinese population.MethodsA longitudinal study consisted of baseline survey and two follow-ups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Zhu found differences in prediabetes by different criteria in a longitudinal study and stated that targeted prevention should be categorized by impaired fasting glucose, impaired glucose tolerance, and elevated HbA1c. [40] Patients with prediabetes are at high risk of developing diabetes and have high prevalence of dyslipidemia, high levels of atherogenic lipids, and increased risk of atherosclerotic cardiovascular disease. For patients with elevated IGT and/or 7-hour plasma glucose, the same intensive treatment of dyslipidemia as recommended for diabetes should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu found differences in prediabetes by different criteria in a longitudinal study and stated that targeted prevention should be categorized by impaired fasting glucose, impaired glucose tolerance, and elevated HbA1c. [40] Patients with prediabetes are at high risk of developing diabetes and have high prevalence of dyslipidemia, high levels of atherogenic lipids, and increased risk of atherosclerotic cardiovascular disease. For patients with elevated IGT and/or 7-hour plasma glucose, the same intensive treatment of dyslipidemia as recommended for diabetes should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, it has been found that anthropometric measures of obesity, such as waist circumference (WC) [11,12] or waist-to-height ratio (WHtR) [13,14] and body mass index (BMI) [9,10] play an important role as risk factors in the manifestation of prediabetes. These measures, derived from simple and accessible indicators, are crucial for identifying patients at risk; this allows for the implementation of strategies to preventively intervene to significantly halt the onset of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Prediabetes is a prominent risk factor for the onset of type 2 diabetes [ 1 ]. Prediabetes is a metabolic complication that is characterized by impaired fasting glucose (IFG), impaired glucose tolerance (IGT) and elevated glycated hemoglobin (HbA1c) [ 2 ]. Literatures have shown that impaired glucose homeostasis is a result of resistance of insulin receptor substrate 1 (IRS-1) to insulin in targeted tissues [ 3 ].…”
Section: Introductionmentioning
confidence: 99%